Micropropagação de Caesalpinia ferrea Martius - Silva, Daniel da (2015)
This project aimed to develop a micropropagation protocol of "Jucá" (Caesalpinia ferrea Mart), an Amazon native species with medicinal, ornamental and timber potential. Seeds were obtained from the Seed Bank belonged to the Laboratoty of Microbiology and Soil Fertility at INPA-Manaus, and after processing, were submerged for 30 minutes in sodium hypochlorite solution of 0.0%, 0.10%, 0.25%, 0.50% and 1.0% and inoculated in MS basal medium. The treatment at 0.25% of sterilizing agent allowed 90% of germination of in vitro seeds. The explants germinated in vitro were targeted and inoculated on MS medium supplemented with 0.1 mg /L of BAP and 0.1 mg /L of IBA. The results indicate that 100% of explants showed shoots and 32.21% developed root systems and total absence of callus. It was observed that 90% of explants derived from yolks developed shoots with 2,73cm and higher proliferation rate (10.21%). The Acclimatization of explants of C. ferrea was possible without the presence of roots grown in vitro, and that the soil is the most suitable substrate for acclimatization with 63.33% of living plants. We conclude that this species can be propagated in vitro, however, further studies are necessary about acclimatization of plants multiplied in vitro in the greenhouse. Keywords: Biotechnology, Vegetal Tissue Culture, in vitro multiplication, Amazon medicinal plant.